Probable values of rise and fall off time of solar cycles 23,24, and 25 - A. G. Elias; N. Ortiz de Adler (Annals of Geophysics, 1996)
From an analysis of the rise and fall off time of solar cycles 4 to 22, a recurrence tendency of 7 cycles is observed in the rise time and, apparently, of 9 cycles in the fall off time. The envelope of these times presents a decreasing amplitude of oscillation. According to this behaviour, the rise and fall length of future solar cycles until cycle 25 can be inferred qualitatively. These values are compared with those obtained with a multiple regression method showing a good agreement.